Paraburkholderia phytofirmans PsJN-Plants Interaction: From Perception to the Induced Mechanisms - Esmaeel, Qassim; Miotto, Lidiane; Rondeau, Marine; Leclère, Valérie; Clément, Christophe; Jacquard, Cédric; Sanchez, Lisa; Barka, Essaid A. (Frontiers in Microbiology, 2018)
The use of plant-associated bacteria has received many scientific and economic attention as an effective and alternative method to reduce the chemical pesticides use in agriculture. The genus Burkholderia includes at least 90 species including pathogenic strains, plant pathogens, as well as plant beneficial species as those related to Paraburkholderia, which has been reported to be associated with plants and exerts a positive effect on plant growth and fitness. Paraburkholderia phytofirmans PsJN, a beneficial endophyte able to colonize a wide range of plants, is an established model for plant-associated endophytic bacteria. Indeed, in addition to its plant growth promoting ability, it can also induce plant resistance against biotic as well as abiotic stresses. Here, we summarized an inventory of knowledge on PsJN-plant interaction, from the perception to the resistance mechanisms induced in the plant by a way of the atypical colonization mode of this endophyte. We also have carried out an extensive genome analysis to identify all gene clusters which contribute to the adaptive mechanisms under different environments and partly explaining the high ecological competence of P. phytofirmans PsJN.